Cobalt Polypyridyl Complexes as Transparent Solution‐Processable Solid‐State Charge Transport Materials. Issue 24 (30th August 2016) - Kashif, Muhammad K.; Milhuisen, Rebecca A.; Nippe, Michael; Hellerstedt, Jack; Zee, David Z.; Duffy, Noel W.; Halstead, Barry; De Angelis, Filippo; Fantacci, Simona; Fuhrer, Michael S.; Chang, Christopher J.; Cheng, Yi‐Bing; et al.
Abstract : Charge transport materials (CTMs) are traditionally inorganic semiconductors or metals. However, over the past few decades, new classes of solution‐processable CTMs have evolved alongside new concepts for fabricating electronic devices at low cost and with exceptional properties. The vast majority of these novel materials are organic compounds and the use of transition metal complexes in electronic applications remains largely unexplored. Here, a solution‐processable solid‐state charge transport material composed of a blend of [Co(bpyPY4)](OTf)2 and Co(bpyPY4)](OTf)3 where bpyPY4 is the hexadentate ligand 6, 6′‐bis(1, 1‐di(pyridin‐2‐yl)ethyl)‐2, 2′‐bipyridine and OTf − is the trifluoromethanesulfonate anion is reported. Surprisingly, these films exhibit a negative temperature coefficient of conductivity (d σ /d T ) and non‐Arrhenius behavior, with respectable solid‐state conductivities of 3.0 S m −1 at room temperature and 7.4 S m −1 at 4.5 K. When employed as a CTM in a solid‐state dye‐sensitized solar cell, these largely amorphous, transparent films afford impressive solar energy conversion efficiencies of up to 5.7%. Organic–inorganic hybrid materials with negative temperature coefficients of conductivity generally feature extended flat π‐systems with strong π–π interactions or high crystallinity. The lack of these features promotes [Co(bpyPY4)](OTf)2+ x films as a new class of CTMs with a unique charge transport mechanism that remains to be explored. Abstract : Thin solid films of a cobalt polypyridyl complex exhibit charge conductivity with a non‐Arrhenius temperature dependence. Solid‐state dye‐sensitized solar cells with efficiencies up to 5.7% are obtained by employing this cobalt complex as a more affordable replacement to the traditionally used 2, 2′, 7, 7′‐tetrakis( N, N ‐di‐ p ‐methoxyphenylamine)‐9, 9′‐spirobifluorene hole transporting material.